Heteronuclear Limit of Strong-Field Ionization: Fragmentation of HeH+ by Intense Ultrashort Laser Pulses - Wustelt, Philipp; Oppermann, Florian; Yue, Lun; Moeller, Max; Stoehlker, Thomas; Lein, Manfred; Gräfe, Stefanie; Paulus, Gerhard G.; Sayler, A. Max (Physical Review Letters, 2018)
The laser-induced fragmentation dynamics of this most fundamental polar molecule HeH+ are measured using an ion beam of helium hydride and an isotopologue at various wavelengths and intensities. In contrast to the prevailing interpretation of strong-field fragmentation, in which stretching of the molecule results primarily from laser-induced electronic excitation, experiment and theory for nonionizing dissociation, single ionization, and double ionization both show that the direct vibrational excitation plays the decisive role here. We are able to reconstruct fragmentation pathways and determine the times at which each ionization step occurs as well as the bond length evolution before the electron removal. The dynamics of this extremely asymmetric molecule contrast the well-known symmetric systems leading to a more general picture of strong-field molecular dynamics and facilitating interpolation to systems between the two extreme cases.
CRIS-Team Scopus Importer:2023-04-20